2017
DOI: 10.4265/bio.22.97
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fungi from an Indoor Environment using Loop-mediated Isothermal Amplification (LAMP) Method

Abstract: Loop-mediated isothermal amplification LAMP is a useful DNA detection method with high specificity and sensitivity. The LAMP reaction is carried out within a short time at a constant temperature without the need for thermal cycling. We developed a LAMP primer set for detecting a wide range of fungi by aligning the sequences of the large subunit ribosomal RNA gene of Candida albicans Ascomycota , Cryptococcus neoformans Basidiomycota , and Mucor racemosus Mucorales . The threshold of C. albicans rDNA as templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The disadvantages of PCR and IC-PCR detection methods are that they require instruments, professional personnel, bacterial enrichment, and genome or plasmid extraction [15,34]. LAMP is a novel amplification approach developed by Notomi et al [35], which is rapid and highly specific, and has been applied for various pathogens, including parasites [36,37], fungi [38], bacteria [20], and viruses [39,40]. The biggest disadvantage of LAMP is that it produces aerosol during detection, leading to many false positives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages of PCR and IC-PCR detection methods are that they require instruments, professional personnel, bacterial enrichment, and genome or plasmid extraction [15,34]. LAMP is a novel amplification approach developed by Notomi et al [35], which is rapid and highly specific, and has been applied for various pathogens, including parasites [36,37], fungi [38], bacteria [20], and viruses [39,40]. The biggest disadvantage of LAMP is that it produces aerosol during detection, leading to many false positives.…”
Section: Discussionmentioning
confidence: 99%
“…This special equipment is expensive and requires professional technical assistance, which largely limits their applications, especially for areas with poor resources. LAMP is a simple detection method that does not require special equipment (unlike PCR or real-time PCR), but it cannot enrich the target substances from the samples, and a commercial kit is also needed to extract the plasmid or genome [37,38]. Moreover, for some special samples, such as sputum, blood, and feces, it is very difficult to accurately and quickly enrich the target substances, and much time and materials are needed during the process [47].…”
Section: Discussionmentioning
confidence: 99%
“…The study reported the sensitivity of LAMP assay was 10 2 copies per 25 ll reaction. The assay can be efficiently used to detect fungi from the environment (Nakayama et al 2017). Another study was carried out by Luo et al (2014) to detect aflatoxins by Aspergillus flavus, Aspergillus parasiticus and Aspergillus nomius.…”
Section: B3cmentioning
confidence: 99%
“…To evaluate the specificity of the LAMPAuris primer set toward C. auris, a panel of 63 strains consisting of 39 species, including 21 filamentous fungi and 18 yeasts, were tested (Tables 2 and 3). For each of the filamentous fungi, total DNA was extracted and purified as described previously (20). For each of the yeast strains, small portions of colonies grown on Sabouraud dextrose agar (SDA) plates were suspended in 25 l distilled water, heated at 100°C for 15 min, and briefly centrifuged.…”
mentioning
confidence: 99%
“…In contrast, none of the filamentous fungi or the other yeast species, including those for which C. auris is commonly misidentified, yielded any amplification signal. To validate the quality of the DNA templates used in the LAMPAuris reactions, LAMP reactions using a panfungal LAMP primer set (20) were run separately; amplifications were detected with templates from each of the tested species (data not shown).…”
mentioning
confidence: 99%